Mycelial Extracts as Sensitive Element for Acoustoelectronic Gas Sensor. (2017) - Kuznetsova, Iren E.; Zaitsev, Boris D.; Shikhabudinov, Alexander M.; Tsivileva, Olga M.; Pankratov, Alexei N.
Abstract: The main problem in development of the acoustoelectronic gas sensors is the search of the elements which are sensitive to the presence of different gases. In this paper we suggest to use for this purpose the piezoelectric quartz resonators with the mycelium films of mushroom Lentinula edodes strain F-249, which was cultivated in synthetic medium. The extract of mycelium was deposited on the surface of the resonator. The measurements of the frequency dependencies of the real and imaginary parts of electrical impedance of the resonator allowed finding the density, elastic constants and viscosity of the films under study. The influence of various gases (ammonia, formaldehyde, ethylacetate) and volatile liquids (acetone, acetic acid, chloroform) on physical properties of the extracts of mushroom Lentinula edodes mycelium has been investigated. It has been found that it is possible to use the mycelium films of mushroom Lentinula edodes prepared by different ways as sensitive film to ammonia, formaldehyde and ethyl acetate.